The Impact of COVID-19 on the Development of the Belt and Road Initiative and China's Foreign Policy - Aryodiguno, Harryanto (KnE Social Sciences, 2022)
This paper analyzes the impact of the COVID-19 pandemic on the Belt and Road Initiative adopted by the Chinese government for infrastructure development and global investment. A literature review was conducted using the perspective of China’s foreign policy as a basis for analysis. The literature used included books, journals, electronic media, and official statements of Chinese officials with qualitative and quantitative data. In this paper, the author reveals the impact of this pandemic on the factors that influence China’s foreign policy and, more specifically, the Belt and Road Initiative policy. This paper concludes that the Belt and Road Initiative has shown strong resilience and vitality in the face of the pandemic. Related projects are constantly advancing, and the associated cooperation has led to many benefits, which have become a bright spot in the haze of the pandemic. Keywords: reform and opening-up, China rise, Belt and Road Initiative, COVID-19